What Affects Sports Participation and Life Satisfaction Among Urban Residents? The Role of Self-Efficacy and Motivation - Yu, Guo; Song, Yu (Frontiers in Psychology, 2022)
In the context of the current COVID-19 pandemic, how can we promote more people to participate in sports to improve physical health and how can we provide people with a sense of well-being to ensure psychological health are pressing issues. This study aims to discover the mechanisms influencing sports participation and life satisfaction among urban residents, focusing on the role of self-efficacy and motivation. A questionnaire survey on sports participation of Shanghai residents in China found that: self-efficacy significantly and positively influenced sports participation; sports participation significantly and positively influenced life satisfaction; motivation positively influenced sports participation and mediated between self-efficacy and sports participation, but sports participation did not mediate between self-efficacy and life satisfaction. Therefore, it is important to enhance people's self-confidence in sports participation and establish the concept of sports for all people, so as to strengthen people's motivation to participate in sports, and to guide people to exercise actively through national fitness, so that more people can be happiness in sports.